Avascular necrosis of the femoral head at 2 years after pertrochanteric fracture surgery: Case report. (February 2016) - Deleanu, Bogdan; Prejbeanu, Radu; Vermesan, Dinu; Honcea, Lucian; Mioc, Mihail Lazar; Tsiridis, Eleftherios; Predescu, Vlad
Abstract: Introduction: The avascular necrosis of the femoral head represents the death of bone tissue due to the lack of blood supply. The disease has a progressive evolution and left untreated leads to femoral head collapse and severe arthritis. Case presentation: We present a case of a pertrochanteric fracture which has been successfully operated with a dynamic interlocking trochanteric gamma nail on the right hip. At 2 years after surgery the patient developed an incipient avascular necrosis of the femoral head. Despite the good positioning of the implant, we considered that the source of the pain was an intolerance of the implant, and thus we removed it. After implant removal, the patient was kept under observation and conservative treatment, to prevent further damage to the right hip and allow the healing to occur. At 6 months after the gamma nail was removed the X-rays revealed advanced avascular necrosis of the femoral head and secondary osteoarthritis on the right hip. The patient underwent surgery with an uncemented total hip arthroplasty. Discussion: There are a few discussions regarding the avascular necrosis of the femoral head. These discussions may include the predisposing risk factors, the treatment of choice and the postoperative complications. Conclusion: The avascular necrosis of the femoral head is a complication of pertrochanteric fractures that can not be foreseen or avoided. The optimal treatment in these cases is uncemented total hip arthroplasty. Highlights: Avascular necrosis of the femoral head. Operative management. Postoperative rehabilitation. Complications.